Neighborhood’s reinvention? Ethnography of the Public Art Gallery at Quinta do Mocho - Raposo, O. (2017)
Quinta do Mocho, located in the city of Loures, has become known by the media as one of the main “problematic neighborhoods” of the metropolitan area of Lisbon, a label based on the alleged relationship of its young residents with drugs trafficking and violent crime. Nowadays, the reasons that made Quinta do Mocho newsworty have become different, as the neighborhood was converted into the largest open-air urban art gallery in Europe, with more than sixty pieces of graffiti decorating this social housing, where about three thousand people live. Incorporated in the Public Art Gallery (GAP), this project began in September 2014, within the urban art festival called “O Bairro I o Mundo, organized by the Teatro Ibisco Association and the Loures City Council. If this project of artistic intervention is changing the Quinta do Mocho image from outside, it is important to find out how the inhabitants, the overwhelming majority coming from former Portuguese colonies, are dealing with these changes. Will the population become involved in the artistic intervention that is developing in the neighborhood? To what extent with the valorization of the neighborhood through art be capable of reconfiguring the place of its residents, especially the young people, in the hierarchy of the city? Based on an ethnographic accompaniment to the guided tours that the young people carry out in the neighborhood, I will reflect on the art, the segregation and dynamics of political-citizen engagement. If artistic expressions are an excellent way to get around the segregations and stigmatization process among the subaltern classes, it is important to discuss its limits, as well the political instrumentalization of art to approaching social problems.